EFEKTIVITAS PROGRAM PRAKTEK LAPANGAN MAHASISWA BERBASIS PENEMPATAN PADA LEMBAGA MITRA DEPARTEMEN PENDIDIKAN LUAR SEKOLAH (Studi Pada Mahasiswa PPL Departemen PLS FIP UPI) - Komar, Oong (PEDAGOGIA, 2017)
Program Field (PPL) as a program that instills applicative capabilities integrated with the entire previous learning experiences into the training program of the performance of all matters relating to the working positions, both teaching and learning activities as well as other tasks. However, the observation while not showing state competence and professional working systematic order. The question is: (1) What is the general profile of each institution used PLS partners PPL? (2) Which PLS PPL partner institutions that have a high tendency PPL effective implementation? (3) What is the level of effectiveness of the PPL student at a partner institution PLS department? This study aims to assess the effectiveness of the PPL student placement based on PLS department partner institutions. Performed using a quantitative approach with data collection questionnaire scale. The results showed the effectiveness of the PPL student placement based on PLS department partner agencies needs to be improved and suggested further implementation of PPL housed at partner institutions whose programs CLC complete or appropriate placement rolling competence PPL expectations.